Editorial-special issue on "Sensor technology for enhancing training and performance in sport" - Kong, P. W. (Sensors, 2023)
Sensor technology opens up exciting opportunities for sports. For example, advancements in motion tracking devices allow monitoring athletes` movement patterns indoors and outdoors [1,2,3]. Wearable sensors offer insightful information on the demands of the sport during both training and competition [4]. Such data are important for coaches and athletes to optimize their training plan, minimize the risk of injuries, and improve sport performance. This Special Issue focuses on the innovative development and application of sensors for enhancing training and performance in sport. We received a total of 9 original and 1 review articles covering a variety of sports, including those on land [5,6,7,8,9,10,11,12,13] and in water [14].